DEVELOPMENT OF THE RUSSIAN ANTI ACCESS/ANTI DENIAL (A2/AD) CONCEPT AS A THREAT TO NATO AND POLAND - RADOMYSKI, Adam Marek (Torun International Studies, 2021)
This article presents an analysis of the development of the Russian Anti Access/Anti Denial concept – A2/AD. The considerations contained in this article focus on identifying the threats that the Russian A2/AD concept creates for NATO and Poland. This article compiles empirical data from scientific publications, formal strategic and doctrinal documents, which allowed to define the A2/AD category, specify its essence and characterize it through the prism of military and non-military forces and resources engaged by Russia in several important operational regions: the Kaliningrad Oblast, Crimea, Syria and the Arctic. The aim of this article is to evaluate the Russian Anti-Access/Anti Denial concept from the perspective of the threats it creates for NATO and Poland. The obtained research results allow us to make the conclusion that when assessing the current external conditions, effective opposition to the Russian A2/AD by NATO will be very difficult to implement. Increasing the capabilities in this area will probably require the individual member states to increase their defense spending, mainly on the modernization and development of their armed forces. In addition to increasing the financial expenditures, increasing the ability to counteract the Russian A2/AD will require proper coordination and integration of the activities of the entire NATO structure around one coherent operational concept. This applies not only to counteracting the Russian A2/AD in Europe but also in other regions of the world, which in the near future may become the theatre of military operations, both classic, asymmetric or hybrid.